2018
DOI: 10.1111/add.14227
|View full text |Cite
|
Sign up to set email alerts
|

Perception of physical attractiveness when consuming and not consuming alcohol: a meta‐analysis

Abstract: Experimental and quasi-experimental studies suggest that consuming alcohol may have a small effect of increasing perceived attractiveness of people of the opposite sex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…Pharmacological effects and the impact of expectancies are dose-dependent; in the case of small quantities, expectancies have a greater role than in the case of large doses, where the chemical effect of the substance might dominate (Alfonso-Loeches and Guerri 2011;Brust 2010;Cederbaum 2012;Guerri and Pascual 2010;Moonat et al 2010;Zahr et al 2011). These two effects are influenced by individual differences: body composition, drinking habits, gender and genetic heritage modulate the pharmacological mechanism (Morean and Corbin 2010), whereas individual expectations, experiences, beliefs and attitudes have an impact on the expectation mechanism (Bowdring and Sayette 2018, Dömötör et al 2015, Szemerszky et al 2013.…”
mentioning
confidence: 99%
“…Pharmacological effects and the impact of expectancies are dose-dependent; in the case of small quantities, expectancies have a greater role than in the case of large doses, where the chemical effect of the substance might dominate (Alfonso-Loeches and Guerri 2011;Brust 2010;Cederbaum 2012;Guerri and Pascual 2010;Moonat et al 2010;Zahr et al 2011). These two effects are influenced by individual differences: body composition, drinking habits, gender and genetic heritage modulate the pharmacological mechanism (Morean and Corbin 2010), whereas individual expectations, experiences, beliefs and attitudes have an impact on the expectation mechanism (Bowdring and Sayette 2018, Dömötör et al 2015, Szemerszky et al 2013.…”
mentioning
confidence: 99%
“…People commonly and strongly endorse social expectancies and social motives for drinking (i.e., drinking to enhance social experiences; Brown et al, 1980; Cooper, 1994; Cooper et al, 2016; King et al, 2023; Kuntsche et al, 2005; Patrick et al, 2011; Votaw & Witkiewitz, 2021) and, consistent with these expectancies and motives, a large and growing literature demonstrates alcohol’s acute social rewards. In both tightly controlled laboratory experimental studies and ecological momentary assessment studies capturing experiences in daily life, alcohol has been shown to increase social bonding, talkativeness, sociability, friendliness, agreeableness, and the perceived physical attractiveness of others (Aan het Rot et al, 2008; Babor et al, 1983; Bowdring & Sayette, 2018a; Fairbairn & Sayette, 2014; Knight & Godfrey, 1993; Lindfors & Lindman, 1987; Lindman, 1982; Sayette et al, 2012; Stitzer et al, 1981) and to enhance aspects of social cognition known to foster connections (e.g., affective empathy and common ground; Dolder et al, 2017; Garrison et al, 2023). Humans have a fundamental need to belong and form social connections (Baumeister & Leary, 1995), and alcohol’s social rewards appear to aid in fulfilling these powerful basic needs (Creswell, 2021; Sayette et al, 2012).…”
Section: Open Practices Statementmentioning
confidence: 99%
“…Notably, these social expectations and motives longitudinally predict alcohol use and alcohol problems (Patrick et al, 2011; Smith et al, 1995). Beyond this survey work, experimental lab work demonstrates that alcohol has robust social facilitative effects, increasing social bonding, sociability, and the perceived attractiveness of others (Bowdring & Sayette, 2018; Sayette et al, 2012). Alcohol's potent ability to foster relationships with others is a critical reason that individuals choose to drink with important implications for understanding AUD risk (Creswell, 2021).…”
Section: Introductionmentioning
confidence: 97%